Alcohol Consumption and Risk of First-Time Venous Thromboembolism in Men and Women - Johansson, Magdalena; Johansson, Lars; Wennberg, Maria; Lind, Marcus (Thrombosis and Haemostasis, 2019)
Background The relationship between alcohol intake and risk of venous thromboembolism (VTE) is unclear. Men and women differ in their drinking habits, which may affect a possible association.Objective This article investigates the association between alcohol consumption, alcohol dependence and VTE in the total population as well as in men and women separately.Methods We performed a prospective, population-based cohort study in northern Sweden. Study participants were 108,025 (51% women) persons aged 30 to 60 years who underwent a health examination between 1985 and 2014. We assessed alcohol consumption and defined alcohol dependence using a questionnaire. The outcome was a validated first-time VTE.Results The mean follow-up time was 13.9 years, and 2,054 participants had a first-time VTE. The mean alcohol consumption was 3.5 standard drinks weekly in men and 1.5 in women. Alcohol dependence was found in 10% of men and 3% of women. There was an association between alcohol consumption (hazard ratio [HR], 1.02; 95% confidence interval [CI], 1.00–1.03 per standard drink weekly) as well as alcohol dependence (HR, 1.27; 95% CI, 1.06–1.52) and VTE after adjustments. In men, the risk of VTE increased over quartiles of weekly alcohol consumption (p for trend 0.02), with a HR of 1.22 (95% CI, 1.01–1.47) for the highest quartile. Alcohol dependence was associated with VTE in men (HR, 1.30; 95% CI, 1.07–1.59). In women, there were no significant associations.Conclusion High alcohol consumption and alcohol dependence were associated with increased risk of first-time VTE in men, but not in women.
Keywords: alcohol drinking; cohort studies; pulmonary embolism; venous thromboembolism; venous thrombosis